P2P Lending Default Settlement in Indonesia and United States - Wicaksono, Lucky Suryo (Universitas Brawijaya, 2024)
This study examines the handling and settlement of defaults in P2P lending in Indonesia and the United States. This study is normative, analysing data on the legal norms embedded in legislation and employing a comparative approach with the United States. The findings reveal significant differences between the two countries in addressing P2P lending defaults. In the United States, defaults are generally managed through a collection process involving an internal team and third-party debt collectors, who must comply with the Fair Debt Collection Practices Act (FDCPA). In contrast, in Indonesia, defaults may be resolved through litigation or non-litigation methods, including mediation through the Alternative Dispute Resolution Institution (LAPS). However, many defaults are not resolved through these formal channels; instead, they are handled by third-party debt collectors. This approach often leads to issues, as no specific law in Indonesia regulates debt collection practices.